Moral Dimension in Character Education: A Comparative Study of Kohlberg and Lickona's Thought on the Formation of Individual Morals and Ethics - Eka Ismaya Indra Purnamanita; Arifatul Ma'ani (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to examine and describe the conceptual framework of character education formulated by Lawrence Kohlberg and Thomas Lickona. Using a qualitative, literature-based approach with descriptive analysis techniques, this study reviews various primary sources and supporting literature related to moral development. The results of the study indicate that Kohlberg constructs moral development into three hierarchical levels—preconventional, conventional, and postconventional—each comprising two stages. Meanwhile, Lickona developed a more comprehensive framework through three main dimensions—moral knowing, moral feeling, and moral action—each containing a number of interrelated components. Although both models yield three major dimensions of character, Lickona’s model offers a more detailed and practical approach in the context of character education.